K-Stability and Kähler-Einstein Metrics - Tian, Gang (Communications on pure and applied mathematics, 2015)
We prove that if a Fano manifold M is K‐stable, then it admits a Kähler‐Einstein metric. It affirms a longstanding conjecture for Fano manifolds. © 2015 Wiley Periodicals, Inc.